ANALYZING THE EFFECT OF TAX CHANGES ON K-POP MERCHANDISE BUYING DECISION - Mardiyah, Fitriatul; Misra, Fauzan (E-Jurnal Akuntansi TSM, 2025)
This study examines the impact of changes in tax regulations on K-Pop fans' purchasing decisions, addressing a research gap by exploring the relationship between taxation and fan behavior, which is typically analyzed from management and marketing perspectives. With Indonesia being one of the countries with the highest number of K-Pop fans, their purchasing behavior may be influenced by tax-related, psychological, and emotional factors, particularly in response to recent tax regulation changes. Using mental accounting theory, this research investigates how fanatical behavior influences purchasing decisions, often leading to economically irrational choices. A survey method was employed, targeting university students in Padang, and multiple linear regression analysis was used for data interpretation. The findings reveal that changes in VAT rates and tax treaties do not significantly affect purchasing decisions, whereas changes in the import duty threshold positively influence the purchase of K-Pop merchandise. These insights provide a deeper understanding of how tax regulations shape consumer behavior, particularly within niche fandom markets.